Adoption of Modern Paddy Farming Practices Among the Farmers in a Mahaweli Settlement Scheme in Sri Lanka - Rupasinghe, Tenne Gedara (1992)
The main purpose of the study was to determine the adoption and level of adoption of modern paddy farming practices among the farmers in the Galnewa Block of System H in the Mahaweli territory of Sri Lanka. The study also attempted to estimate the relationship between adoption and yield. In addition, the study examined the relationships between adopt ion and ascertained factors derived from factor analysis. It further analysed the extent of adoption and non-adoption, the characteristics of adopters and non-adopters, the practices which were adopted and not adopted, and reasons for nonadoption. The study used the survey method supplemented by observations,unstructured interviews, and secondary data.